Effectiveness of virtual clinical simulation in palliative care education for nursing students: Protocol of a randomized controlled trial - Zhixiang Sun; Pingpin Wen; Lu Zhang; Xiaoli Zhang; Xinyu Yang; Chunyan Liu; Jing Fu; Meifang Yang (PLoS ONE, 2026)
Background Palliative care often involves nursing for complex patient groups at the end of life, which requires specialized knowledge and ethical considerations. Therefore, it is full of challenges when carrying out practical teaching. Nursing students, as the next generation of healthcare professionals, will assume the important responsibility of providing specialized health services related to end-of-life care (EOLC). A deficit in direct clinical practice may impede the acquisition of essential knowledge and ability in palliative care for nursing students.Virtual clinical simulation (VCS) is acknowledged as an effective educational tool in nursing education. However, its application in palliative care education remains underexplored, particularly through rigorous study designs. While VCS has been tested in areas such as acute care or clinical deterioration, there is a global scarcity of randomized controlled trials (RCTs) evaluating its effectiveness in palliative care education, and relevant research in China remains limited. In this study protocol, we hypothesize that VCS will improve nursing students’ knowledge, ability, and attitudes regarding palliative care, compared to conventional teaching alone. Methods This study protocol outlines a prospective RCT aimed at evaluating the educational benefits of incorporating VCS into the curriculum for nursing students at a medical university in southwestern China.These students, registered for the elective Cultural Perspectives on Death and End-of-Life Education will be systematically invited to join this research. The study will randomly assign 96 students into two distinct groups: a control group and an intervention group, each comprising 48 students. The control group will participate solely in conventional classroom teaching, whereas the intervention group will receive both conventional classroom teaching and enhanced learning through an additional VCS system, aimed at improving their knowledge, ability and attitudes regarding palliative care. The intervention is grounded in experiential learning theory, which supports the use of simulated environments to foster reflective practice and skill acquisition. Assessments will occur at baseline and post-intervention of the VCS, with the primary metrics for evaluation encompassing variations in students’ knowledge, ability, and attitudes concerning palliative care, as well as their satisfaction with VCS pedagogy and confidence in applying their newly acquired skills and knowledge in practical medical settings. As this is a protocol paper, no outcome data are yet available. Discussion VCS may be an effective tool to enhance nursing students’ palliative care knowledge, ability, and attitudes, and it provides scientific evidence to inform nursing students in selecting the most appropriate approach for their palliative care education. Trial registration Chinese Clinical Trial Registry: ChiCTR2500096377, Registered on January 22, 2025.